Boeravinone F, Withanolide D, and Chitranone are a Potential Antagonist of Angiotensin Receptor 1 Insilico for Hypertension Treatment - Ningtyas, Febri; Wulandari, Sri; ., Balqis (Nexus Kedokteran Translasional, 2017)
Introduction: Hypertension is a silent killer which can cause complications such as heart diseases, stroke, and chronic kidney diseases. Olmesartan is a one of the Angiotensin Receptor Blockers (ARBs) for an alternative treatment of hypertension. However, this drug has low bioavailability, short duration, and partial agonist against angiotensin 1 receptor (AT1). Indonesia has more than 6.000 phytochemicals which are derived from various herbal plants but their therapeutic effects are unknown. Molecular docking is an initial step to find new drug candidates that have shorter time and lower cost. Therefore, this study aimed to identify phytochemicals as an AT1 antagonist through molecular docking for hypertension treatment.  Methods: This was a bioinformatics study. Research samples were all phytochemicals registered in HerbalDB, had 3 dimention structure, and met criteria of Lipinskis rule of five. Olmesartan was used as a standard ligand and obtained from PubChem. AT1 receptor was downloaded from Protein Data Bank. Validation of receptor-standard ligand binding complexes was done by using Autodock Vina 1.1.2 five times. Docking results were visualized using Pymol 1.7 and Chimera 1.10. Data were analyzed using  docking scores, binding sites, molecular conformation, and criteria of Lipinskis rule of five.  Results: Olmesartan had -9.9 Kcal/mol docking score and interacted with the AT1 receptor at Tyr35, Trp84, dan Arg167 residues. Boeravinone F (-10,2 Kcal/mol), Chitranone (-10,5 Kcal/mol), and Withanolide D (-10,8 Kcal/mol) had lower docking score than olmesartan. These phytochemicals had binding sites as same as olmesartan except Chitranone with an additional binding site  at Asp281 residue. The phytochemicals  had different conformation from olmesartan but had similarity of chemical properties with olmesartan.  Conclusions: Boeravinone F, Chitranone, and Withanolide D can be potential as an AT1 receptor inhibitor insilico for hypertension treatment. Keywords: hypertension, AT1 receptor, olmesartan, phytochemicals, molecular docking.